Application of cone beam computed tomography in facial soft tissue thickness measurements for craniofacial reconstruction - Meundi, Manasa Anand (J Oral Maxillofac Pathol, 2019)
CONTEXT: The paradigm shift from two- to three-dimensional imaging has marked the beginning of a new era in diagnosis. Newly developed cone-beam computed tomography (CBCT) designed specifically to visualize maxillofacial pathologies is being used in forensic investigations also. Facial reconstruction is a specialized forensic technique to identify the deceased from the unknown skull. It is dependent on population-specific facial soft tissue thicknesses. AIMS: This study aims to propose the mean dataset of facial soft tissue thickness for South Indian population by utilizing CBCT. It also aims to evaluate the sex and racial differences in the values if any. SETTINGS AND DESIGN: This descriptive study was conducted on CBCT scans of South Indians. MATERIALS AND METHODS: Eighty CBCT scans of South Indian adults aged 18–80 years were selected. Facial soft tissue thickness measurements at 34 craniometric landmarks were carried out. STATISTICAL ANALYSIS: Descriptive statistics was done. Student's t-test estimated the differences of soft tissue thickness between the sexes; bilateral measurements and also racial differences. Tukey's honest significant difference test was used for multiple comparisons among Indian studies. RESULTS: Males had thicker soft tissue than females in most of the landmarks. Differences in the bilateral soft tissue thicknesses were negligible. Indians had thicker facial tissues than the Koreans and CBCT was found efficient in measuring soft tissue thickness. CONCLUSION: The present study provides facial soft tissue thickness dataset using CBCT which will be useful in forensic facial reconstructions of South Indian population as well as in maxillofacial and plastic reconstructive surgeries.